ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN BERTEMPAT TINGGAL DI KOTA BEKASI BAGI PENDUDUK MIGRAN BERPENGHASILAN RENDAH YANG BEKERJA DI KOTA JAKARTA - Annisa Purbosari; Mulyo Hendarto (Diponegoro Journal of Economics, 2012)
ABSTRACT This study aims to analyze the influence of price perseption, accessibility, public utility, surroundings, and personal income toward residential decision for migrant with low income who lived in Bekasi City and worked in Jakarta City. Most of the migrant who lived in Bekasi City and worked in Jakarta City called as consolidators, according to the mobility residential, the consolidators are people who have lived longer in urban area. They will be opting residential in suburban area than urban area caused by achievable house price.This study using binary logistic regression analysis. Primary data which used in this study came from questionnaire that distributed for a hundred respondents who agree with sample criteria. Interpretation of accounting statistic also supported by interview result to some respondents who become key person in this study. Dependent variable in this study organized as nominal scale. Whole of independent variables in this study used ordinal scale that changed to be interval scale through Successive Interval Method (SIM), except personal income variable. Based on the result of classification table accounting, data can predicted correctly amounts 79%. Trough Wald Test, independent variables which had an influence on its dependent variables are price perception variable, public utility, surroundings and personal income. The most independent variable which had an influence on its dependent variable is public utility.